2022
DOI: 10.3389/fendo.2022.951570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liraglutide or lifestyle interventions combined with other antidiabetic drugs on abdominal fat distribution in people with obesity and type 2 diabetes mellitus evaluated by the energy spectrum ct: A prospective randomized controlled study

Abstract: ObjectiveTo study the effects of liraglutide or lifestyle interventions combined with other antidiabetic drugs on glucose metabolism and abdominal fat distribution in patients with obesity and type 2 diabetes mellitus (T2DM).MethodsFrom April 30, 2020, to April 30, 2022, a prospective randomized controlled study was carried out at the Endocrinology Department of Beijing Hospital, the National Center of Gerontology. According to the in- and exclusion criteria and by the random table method, revisited T2DM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Similar results came from Yu et al (120). They enrolled a population of patients with a BMI > 28 kg/m 2 with a prior diagnosis of DM II who had not undergone lifestyle interventions.…”
Section: Principal Side Effectssupporting
confidence: 68%
See 1 more Smart Citation
“…Similar results came from Yu et al (120). They enrolled a population of patients with a BMI > 28 kg/m 2 with a prior diagnosis of DM II who had not undergone lifestyle interventions.…”
Section: Principal Side Effectssupporting
confidence: 68%
“…They were divided into a study group (receiving liraglutide) and a control group (undergoing lifestyle interventions). After 12 weeks of follow-up, the liraglutide group obtained a more significant reduction of VTA calculated by the energy spectrum CT (−7.1 ± 10.17 cm 2 in the study group vs. 0.91 ± 16.59 cm 2 in the control group) (120).…”
Section: Principal Side Effectsmentioning
confidence: 87%
“…[ 9 , 10 ] GLP-1 receptors are distributed in the gastrointestinal tract, cardiomyocytes, endothelial cells, and sinus node. [ 11 , 12 ] Therefore, liraglutide may exert cardioprotective effects by modulating cardiac function and preserving cardiomyocytes. Studies have demonstrated the efficacy of liraglutide in preventing and treating vascular complications of diabetes and alleviate myocardial damage.…”
Section: Introductionmentioning
confidence: 99%